O desespero e a angústica na filosofia de Kierkegaard - Oliveira, Ranis Fonseca de (2009)
This thesis proposes to investigate, with mainstay in theoretical research and literature, the despair and anguish, based on the philosophy of Kierkegaard (1.813-1.855). These two issues are discussed by him in La Maladie the La Mort, under the pseudonym Anti-Climacus, and in Le concept d'Angoisse under the pseudonym of Vigilius Haufniensis. Both the despair, as the existential anguish are real problems which, sooner or later, the individual, as possessor of mind, hopelessly experience and are therefore aspects of the human condition. Kierkegaard understood the desperation as a deadly disease and identifies it with sin, whose faith is the antidote. Already the anguish is understood as the feeling that accompanies all human decisions